Sustainable Development Goals and Archival Policies: the role of municipal archives in the 2030 Agenda - Carvalho Pazin Vitoriano, Marcia Cristina de [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2021)
This article aims to discuss how the creation of archival policies at the municipal level can contribute to the sustainable development goals, notably with the 2030 Agenda, and the role of archives in this process. To fulfill this objective, bibliographic research was used as a methodological procedure, based on the analysis of goal 11, to make cities and communities safe, resilient and sustainable, and goal 16, to promote peace, justice and effective institutions, and its relation to the concept of archival policies. As a result, the constituent elements of municipal archival policies that relate to the 2030 Agenda and the possible intersections between sustainable development goals and Archival Science as field of research.
Keywords: Municipal archive; Archival policy; 2030 Agenda; Sustainable development